Agrarian involution, domestic economy and women: rural dimension of the Asian crisis - Nathan, Dev; Kelkar, Govind (1999)
Seeing the Asian crisis in only its urban dimensions, it is very easy to conclude that the crisis affects mainly men who have lost their jobs in construction. But though that statement is not true even of the urban economy, when the rural economy is brought into the picture, the role of the domestic economy and of women within it are both sharply brought out. In order to comprehend the rural dimensions of the Asian crisis, the authors take the example of Thailand, with some supplementary material from Malaysia and Indonesia. - Reproduced
Keywords: Women; Agrarian structure; Economic recession